Polynomial Boundary Perturbation for Optimal Plastic Design of Heads of Plane Tension Members - Egner, W. (Engineering Transactions, 1996)
The paper presents the boundary perturbation method applied to optimaI plastic shape design. Perfect plasticity is assumed. The procedure consists of two steps: determination of a class of fully plastic solutions in the limit state, and then the choice of the optimaI shape from among those solutions. A trigonometric polynomial with n terms is assumed for the general solution. FinaI resuIts are given for a binomial. Moreover, a further step towards optimization is done by using extrapolation. The results are verified by the ADINA program.